2019
DOI: 10.1152/ajprenal.00331.2018
|View full text |Cite
|
Sign up to set email alerts
|

Micro-CT imaging and structural analysis of glomeruli in a model of Adriamycin-induced nephropathy

Abstract: Glomeruli number and size are important for determining the pathogenesis of glomerular disease, chronic kidney disease, and hypertension. Moreover, renal injury can occur in specific cortical layers and alter glomerular spatial distribution. In this study, we present a comprehensive structural analysis of glomeruli in a model of Adriamycin (doxorubicin) nephropathy. Glomeruli are imaged (micro-CT at 10 × 10 × 10 μm3) in kidney specimens from C57Bl/6 mouse cohorts: control treated with saline ( n = 9) and Adria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
(70 reference statements)
3
11
0
Order By: Relevance
“…However, this did not reveal any disadvantages in the presentation of the vascular architecture by MicroCT measurement. Similar to studies performed in mice and rats, heterogenous perfusion was observed especially in smaller blood vessels, which has been described as one of the major limitations of MicroFil 53–56 . Another limitation is the resolution of the MicroCT scanner.…”
Section: Discussionsupporting
confidence: 66%
“…However, this did not reveal any disadvantages in the presentation of the vascular architecture by MicroCT measurement. Similar to studies performed in mice and rats, heterogenous perfusion was observed especially in smaller blood vessels, which has been described as one of the major limitations of MicroFil 53–56 . Another limitation is the resolution of the MicroCT scanner.…”
Section: Discussionsupporting
confidence: 66%
“…5 In certain animal models, deep glomeruli are larger than superficial glomeruli, 628 and glomeruli of intermediate depth. 9,10 Several human autopsy studies of glomerular volume have also concluded that deep glomeruli are larger, 11213 although one study has found superficial glomeruli to be larger in older adults. 14 Age-related glomerulosclerosis appears to occur predominantly in the superficial cortex.…”
mentioning
confidence: 99%
“…Increased glomeruli volume, as representative of the renal and functional units of the kidney, can compensate for lost glomeruli function, adapt to new conditions, and remove toxins from the body [55,56]. Glomeruli undergo hyperfiltration to control the conditions and maintain filtration, resulting in an increase in glomerular volume [57].…”
Section: Discussionmentioning
confidence: 99%